Managing Diversity Through Human Resource Management: A USA Perspective and Conceptual Framework - Hossain, Mohammad Ikbal (Archives of Business Research, 2023)
This research paper explores the dynamic landscape of managing diversity through Human Resource Management (HRM), focusing on the United States context. Evolving from a compliance concern to a strategic imperative, diversity plays a pivotal role in enhancing innovation, creativity, and problem-solving in contemporary workplaces. By aligning HRM practices with diversity initiatives, organizations can leverage the strengths of a heterogeneous workforce. The challenges posed by communication barriers, stereotypes, and resistance to change necessitate a strategic HRM approach. Tailored recruitment, training, performance management, and leadership development are key elements of this approach. Creating an inclusive organizational culture, facilitated by HRM through leadership commitment, anti-discrimination policies, and open communication, is pivotal. Legal and ethical considerations provide a foundation for this journey. The potential long-term benefits of effective diversity management include improved performance, innovation, talent attraction, and social responsibility. This paper underscores the importance of managing diversity through HRM as an investment in organizational success and a more inclusive society.